2007
DOI: 10.1111/j.1469-8137.2007.02234.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular toxicity of elsinochrome phytotoxins produced by the pathogenic fungus, Elsinoë fawcettii causing citrus scab

Abstract: Summary• Elsinochromes are the red/orange pigments produced by many Elsinoë fungal species and are structurally similar to the phytotoxin, cercosporin. Here, pigments were extracted from cultures of a citrus pathogen, Elsinoë fawcettii and tested for cellular toxicity.• On irradiation with light, elsinochromes rapidly killed suspension cultured citrus and tobacco cells. The toxicity was decreased by adding the singlet oxygen ( 1 O 2 ) quenchers (bixin (carotenoid carboxylic acid), DABCO (1, 4-diazabicyco octan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…The biological function of elsinochromes as phytotoxins toward host and nonhost plant cells both in vitro and in vivo was recently documented to be light-dependent (Liao & Chung, 2008a). Their cellular toxicities were further shown to be mediated through production of reactive oxygen species such as superoxide and singlet oxygen, which may damage cell membranes and induce electrolyte leakage from the cells (Liao & Chung, 2008a). Further studies employing molecular and genetic approaches unambiguously confirmed a critical role for elsinochromes in lesion development and fungal pathogenesis.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…The biological function of elsinochromes as phytotoxins toward host and nonhost plant cells both in vitro and in vivo was recently documented to be light-dependent (Liao & Chung, 2008a). Their cellular toxicities were further shown to be mediated through production of reactive oxygen species such as superoxide and singlet oxygen, which may damage cell membranes and induce electrolyte leakage from the cells (Liao & Chung, 2008a). Further studies employing molecular and genetic approaches unambiguously confirmed a critical role for elsinochromes in lesion development and fungal pathogenesis.…”
Section: Introductionmentioning
confidence: 90%
“…The wild-type CAL WH-1 isolate of Elsinoë fawcettii, used for cloning, transformation and targeted gene disruption, was cultured from scab-affected calamondin (Citrus madurensis Lour.) fruit in Florida and has been previously characterized (Liao & Chung, 2008a). The genetically modified EfPKS1 disruptant (D4) and two complementation strains (C1 and C2) were reported in a previous study (Liao & Chung, 2008b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strain used in our study, Lu949, takes about 5 days to build colonies 0.5 cm in diameter and is not able to overgrow the agar plate if only a piece of mycelium is transferred as the inoculum. This has also been described for isolates of the related species Sphaceloma fawc- ettii, which forms Ͻ10-mm colonies in 30 days (28). The fungus synthesizes large amounts of exopolysaccharides, making it difficult to separate the mycelium from the culture medium.…”
Section: Discussionmentioning
confidence: 99%